Fertilization Recommendations for Crisphead Lettuce Grown on Organic Soils in Florida - George Hochmuth; Ed Hanlon; Russell Nagata; George Snyder; Tom Schuenemann; Mabry McCray; German Sandoya (EDIS)
This 8-page publication presents UF/IFAS recommendations for fertilization of crisphead lettuce on organic soils in Florida. Written by George Hochmuth, Ed Hanlon, Russell Nagata, George Snyder, Tom Schueneman, J. Mabry McCray, and German Sandoya, and published by the UF/IFAS Horticultural Sciences Department, revised January 2023.